2015
DOI: 10.1021/cb5009348
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Substrate Specificity and Regiochemistry in the MycF/TylF Family of Sugar O-Methyltransferases.

Abstract: Sugar moieties in natural products are frequently modified by O-methylation. In the biosynthesis of the macrolide antibiotic mycinamicin, methylation of a 6′-deoxyallose substituent occurs in a stepwise manner first at the 2′- and then the 3′-hydroxyl groups to produce the mycinose moiety in the final product. The timing and placement of the O-methylations impact final stage C-H functionalization reactions mediated by the P450 monooxygenase MycG. The structural basis of pathway ordering and substrate specifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…The ribose moiety of the cofactor establishes a bidentate interaction with the side-chain carboxyl of Asp71, closely resembling the contacts observed for Asp122 from NovP and Asp113 from MycF (SI Appendix, Fig. S10 B and C) (30,31). The hydroxyl groups of the ribose engage also in hydrogen bonds with Gly75 and the side chain of Thr100, the latter via a water molecule.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…The ribose moiety of the cofactor establishes a bidentate interaction with the side-chain carboxyl of Asp71, closely resembling the contacts observed for Asp122 from NovP and Asp113 from MycF (SI Appendix, Fig. S10 B and C) (30,31). The hydroxyl groups of the ribose engage also in hydrogen bonds with Gly75 and the side chain of Thr100, the latter via a water molecule.…”
Section: Resultssupporting
confidence: 56%
“…The Active Site and the Mechanism of Action of MeT1. The closest structural MeT1 homologs are divalent metal-dependent O-MTases (Table 2), often containing a magnesium ion bound at the active site or displaying preference for this metal in activity assays (30,(32)(33)(34)(35). In the SAH-bound MeT1 structure a magnesium ion could be identified, coordinated by the imidazole group of His169, the side-chain carboxylates of the highly conserved Asp170 and Asp141, two solvent molecules, and a molecule of glycerol, in an octahedral arrangement ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…grouped the aligned sequences of 13 experimentally characterized TylF family members according to their substrate structures and methylation sites. They found that two amino acid residues (indicated by a pentacle in Figure S1), Trp58 (NovP number) and Gln246 (MycF number), were highly correlated with the regiospecificity of methyl transfer . Gln246 forms a hydrogen bond with the 4′‐hydroxy group and is conserved among 3′‐OMTs, but is replaced by smaller polar amino acids (Asp or Thr) in 4′‐OMTs.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we observed that AlmCII could methylate a 4,6‐dideoxysugar to give chalcose, which is the first example of a TylF member using a sugar without a 4′‐hydroxy group as a substrate. It has been proposed that 3′‐OMT has a preference for substrates with 3′‐ and 4′‐ syn ‐hydroxy groups located on the opposite face of the glycosidic bond, whereas 4′‐OMT requires anti ‐hydroxy groups at the 3′ and 4′ positions and needs the methylation site and glycosidic bond on the same face . Given the essential role of metal ions in maintaining AlmCII catalytic activity, lack of a 4′‐hydroxy in the substrate demethylchalcose would require an additional hydroxy group to serve as a metal ligand, which might be mediated by the 2′‐hydroxy of the sugar ring or a water molecule near the active site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation